An evaluation of important criteria for measuring the facade condition of old shophouses in Malaysia - Abd Rahman, Sa’afilah; Abdul Rahman, Mohammad Ashraf; Adnan, Suraya Hani (Politeknik Malaysia, 2017)
Preserving the facade of the old shop houses is important to reflect the image of an attractive townscape. Be-sides having a unique architectural motif, the facade of an old shop houses also has a high heritage value, particularly in terms of how it was built. Therefore, it is desirable to ensure the facade is always in good condition. However, it is difficult to determine the facade of the old shop houses that whether they are in good condition or not. This is because there are no specific criteria used to classify the condition of the facade. Therefore, this study aims to establish a system of criteria for which the facade of the old shop houses that can be assessed and classified in a comprehensive and sustainable. A total of 74 respondents from various professional fields including industry practitioners and academics have been involved in com-pleting the questionnaire. The results of this study will then be used as a basis for the establishment of the classification model for building facade of old shop houses in Malaysia.